2017
DOI: 10.1093/ije/dyx176
|View full text |Cite
|
Sign up to set email alerts
|

Declining exposures to lead and cadmium contribute to explaining the reduction of cardiovascular mortality in the US population, 1988–2004

Abstract: Environmental declines in lead and cadmium exposures were associated with reductions in cardiovascular mortality in US adults. Given the fact that lead and cadmium remain associated with cardiovascular disease at relatively low levels of exposure, prevention strategies that further minimize exposure to lead and cadmium may be needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
62
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 49 publications
(57 reference statements)
6
62
2
Order By: Relevance
“…As discussed in several reviews and reports (EFSA 2010;Navas-Acien et al 2007;NTP 2012;Solenkova et al 2014), a number of studies have shown associations between environmental lead exposure and cardiovascular disease and mortality in cohorts with low-level lead exposure (B-Pb concentrations <50 lg=L). Five American studies on low-level environmental lead exposure (NHANES data) showed consistent associations between B-Pb concentrations and cardiovascular mortality (Lanphear et al 2018;Lustberg and Silbergeld 2002;Menke et al 2006;Ruiz-Hernandez et al 2017;Schober et al 2006). An increased risk of cardiovascular mortality has also been found at high levels of lead exposure in several occupational cohorts (Navas-Acien et al 2007;Skerfving and Bergdahl 2015).…”
Section: Discussionmentioning
confidence: 97%
“…As discussed in several reviews and reports (EFSA 2010;Navas-Acien et al 2007;NTP 2012;Solenkova et al 2014), a number of studies have shown associations between environmental lead exposure and cardiovascular disease and mortality in cohorts with low-level lead exposure (B-Pb concentrations <50 lg=L). Five American studies on low-level environmental lead exposure (NHANES data) showed consistent associations between B-Pb concentrations and cardiovascular mortality (Lanphear et al 2018;Lustberg and Silbergeld 2002;Menke et al 2006;Ruiz-Hernandez et al 2017;Schober et al 2006). An increased risk of cardiovascular mortality has also been found at high levels of lead exposure in several occupational cohorts (Navas-Acien et al 2007;Skerfving and Bergdahl 2015).…”
Section: Discussionmentioning
confidence: 97%
“…The impact of Pb exposure on increased risk of CVD mortality has been observed in several epidemiological studies (Aoki et al 2016;Khalil et al 2009;Lanphear et al 2018;Menke et al 2006;Ruiz-Hernandez et al 2017;Schober et al 2006;Weisskopf et al 2015). In addition, the U.S.…”
Section: Introductionmentioning
confidence: 92%
“…EPA 2013). Recent evidence has suggested that exposure to Pb in adults can result in adverse cardiovascular impacts, including increases in hypertension (Muntner et al 2005;Navas-Acien et al 2008), coronary heart disease (Jain et al 2007), cardiovascular disease (CVD) (Chowdhury et al 2018;Guallar et al 2006;Muntner et al 2005;Navas-Acien et al 2004), and CVD-related mortality (CVD mortality) (Aoki et al 2016;Lanphear et al 2005;Menke et al 2006;Ruiz-Hernandez et al 2017). Mechanisms by which Pb may increase risk of death due to cardiovascular disease have been studied in in vitro and in vivo studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concomitant with these reductions, cardiovascular mortality rates in the US decreased by 43% from 1988-94 to 1999-2004. 9 An analysis that accounted for traditional cardiovascular disease risk factors, showed that 32% of this reduction in cardiovascular mortality could be explained by the decline in lead and cadmium exposures. 9 The health impact of recent reductions in arsenic exposure, 10 however, has not been evaluated.…”
mentioning
confidence: 99%